2013
DOI: 10.1590/0074-0276130084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of plasmid-mediated quinolone resistance determinants among oxyiminocephalosporin-resistant Enterobacteriaceae in Argentina

Abstract: High quinolone resistance rates were observed among oxyiminocephalosporin-resistant enterobacteria. In the present study, we searched for the prevalence of plasmid-mediated quinolone resistance (PMQR) genes within the 55 oxyiminocephalosporin-resistant enterobacteria collected in a previous survey. The main PMQR determinants were aac(6')-Ib-cr and qnrB, which had prevalence rates of 42.4% and 33.3%, respectively. The aac(6')-Ib-cr gene was more frequently found in CTX-M-15-producing isolates, while qnrB was ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
2
11
0
1
Order By: Relevance
“…overall PMQR prevalence found here was similar to that observed in phenotypically unselected clinical enterobacteria from Spain (6.4%) 22 and was well below those found in the two earlier surveys from Argentina, namely 57% 23 and 60%, 24 because both studies were based on selected isolates with resistance/decreased susceptibility to quinolones and ESC resistance, respectively.…”
Section: Occurrence and Prevalence Of Pmqr Genessupporting
confidence: 84%
See 1 more Smart Citation
“…overall PMQR prevalence found here was similar to that observed in phenotypically unselected clinical enterobacteria from Spain (6.4%) 22 and was well below those found in the two earlier surveys from Argentina, namely 57% 23 and 60%, 24 because both studies were based on selected isolates with resistance/decreased susceptibility to quinolones and ESC resistance, respectively.…”
Section: Occurrence and Prevalence Of Pmqr Genessupporting
confidence: 84%
“…21,22 In regard to Argentina, only two surveys were reported and they addressed PMQR prevalence in clinical enterobacteria with resistance/decreased susceptibility to quinolones 23 or ESC resistance. 24 Here, we report a large nationwide study based on a point prevalence collection of 1058 unselected clinical enterobacteria that we conducted to estimate the prevalence of all the PMQR genes currently known.…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, qnrB1, qnrB2, qnrB4, qnrB6, qnrB10, qnrB19, and qnrS have been found. [36][37][38] In Bolivia, qnrS and qnrB; 39,40 in Peru, qnrB19 and qnrS; 40,41 in Uruguay, qnrA1, qnrB1, qnrB4, qnrB8-like, qnrB13, and qnrB17; 14,42 and in Venezuela qnrB19, 43 have been reported. The qnr genes have been described in a variety of microorganisms isolated either from colonization, or from nosocomial and community-acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in the world, the qnr B6 gene has been detected in South Korea in a strain of Enterobacter aerogenes producing broad spectrum β-lactamases from a collection of 644 enterobacteriaceae from 12 clinical laboratories [20]. Similarly, in Argentina, Cruz et al [21] reported the presence of qnr B6 in 5% of enterobacteriaceae that produce broad spectrum β-lactamase. Also, in Morocco, the qnr B6 gene was detected in 0.9% of strains producing extended spectrum β-lactamasess tested in the work of Jamali et al [22].…”
Section: Discussionmentioning
confidence: 99%